KETAHANAN SOBEK KERTAS DARI PULP CAMPURAN SABUT KELAPA (Cocos nucifera) DAN PELEPAH PISANG KEPOK (Musa paradisiaca Linn) - Sartika Nur Aisyah; Ramli Ramli; Marlinda Marlinda (Politeknik Negeri Samarinda, 2021)
In general, the main material for making paper making is cellulose. Coconut coir waste contains 23,87% cellulose and kepok banana stem contains 64% cellulose, so that has the potential as an alternative raw material in the manufacture of paper pulp. Kepok banana peels contains 12,8% so it can be used as an adhesive (binder) to increase paper quality. The purpose of this study was to determine the best concentration of cooker solution NaOH in the mixture of coconut coir and banana smelter in producing the best pulp in accordance with SNI 0698:2010 and find out the effect of the concentration of cooking solution NaOH on the resistance of composite paper tear. A mixture of coconut coir and 120 g of banana smelter with a ratio of 40:80 cooked for 4 hours at a temperature of 100 ° C by varying the concentration of cooking solution NaOH 2%, 4%, 6%, 8% and 10%. Then the resulting pulp is printed into paper with the addition of a 35 g banana peel binder. The results in this study found that the best concentration of cooking solution NaOH at a concentration of 8% with cellulose levels of 81.80%, lignin levels of 13.34%, water content of 6.63%, ash content of 2.79% and paper tear resistance of 4393.54 mN.